Given data :
a₃ = 9/16
aₓ = -3/4 · aₓ₋₁
Where x is the number of terms ('x' is also written as 'n')
To find the 7th term (a₇):
We know that aₓ = -3/4 · aₓ₋₁
So,
a₃ = -3/4 · a₃₋₁
a₃ = -3/4 · a₂
9/16 = -3/4 · a₂
a₂ = 9/16 × -4/3
a₂ = -36/48
a₂ = -3/4
Again,
aₓ = -3/4 · aₓ₋₁
a₄ = -3/4 · a₄₋₁
a₄ = -3/4 · a₃
a₄ = -3/4 · 9/16
a₄ = -27/64
a₄ = -27/64
For a₅,
aₓ = -3/4 · aₓ₋₁
a₅ = -3/4 · a₅₋₁
a₅ = -3/4 · a₄
a₅ = -3/4 × -27/64
a₅ = 81/256
For a₆,
aₓ = -3/4 · aₓ₋₁
a₆ = -3/4 · a₆₋₁
a₆ = -3/4 · a₅
a₆ = -3/4 × 81/256
a₆ = -243/1024
For a₇,
aₓ = -3/4 · aₓ₋₁
a₇ = -3/4 · a₇₋₁
a₇ = -3/4 · a₆
a₇ = -3/4 × -243/1024
a₇ = 729/4096
In the equation 3.4a = 57.8, a is equal to: 17.
Answer:
The area of trapezoid is 32 inches^2
Step-by-step explanation:
Parallel base 1 = a = 3 inches
Parallel base 2 = b = 5 inches
Height of trapezoid = 8 inches
We need to find area of trapezoid
The formula used is: ![Area\:of\:trapezoid=\frac{a+b}{2}\times h](https://tex.z-dn.net/?f=Area%5C%3Aof%5C%3Atrapezoid%3D%5Cfrac%7Ba%2Bb%7D%7B2%7D%5Ctimes%20h)
Now putting the values and finding area of trapezoid
![Area\:of\:trapezoid=\frac{a+b}{2}\times h\\Area\:of\:trapezoid=\frac{5+3}{2}\times 8\\Area\:of\:trapezoid=\frac{8}{2}\times 8\\Area\:of\:trapezoid=4\times 8\\Area\:of\:trapezoid=32](https://tex.z-dn.net/?f=Area%5C%3Aof%5C%3Atrapezoid%3D%5Cfrac%7Ba%2Bb%7D%7B2%7D%5Ctimes%20h%5C%5CArea%5C%3Aof%5C%3Atrapezoid%3D%5Cfrac%7B5%2B3%7D%7B2%7D%5Ctimes%208%5C%5CArea%5C%3Aof%5C%3Atrapezoid%3D%5Cfrac%7B8%7D%7B2%7D%5Ctimes%208%5C%5CArea%5C%3Aof%5C%3Atrapezoid%3D4%5Ctimes%208%5C%5CArea%5C%3Aof%5C%3Atrapezoid%3D32)
So, the area of trapezoid is 32 inches^2
Answer:
Point R
Step-by-step explanation:
Go back 12 points
Answer:
Step-by-step explanation:
<u>Statements </u> <u> Reasons</u>
1) QS =42 Given
2) QR + RS = QS Segment Addition Postulate
3) (x + 3) + 2x = 42 Substitution Property
4) 3x + 3 = 42 Simplify
5) 3x = 39 Subtraction Property of Equality
6) x=13 Division Property of Equality
Explanation:
We have given QS=42. We have to prove that x=13
We will use Segment Addition Postulate which states that given 2 points Q and S, a third point R lies on the line segment QS if and only if the distances between the points satisfy the equation QR + RS = QS.
Then we will substitute the values in the defined postulate.
where QR= x+3
RS=2x
QS=42
QR+RS=QS
(x+3)+2x= 42
Now simplify the expression by opening the brackets.
x+3+2x=42
3x+3=42
Now subtract 3 from both sides.
3x+3-3=42-3
3x=39
divide both sides by 3.
3x/3 =39/3
x=13..